Rekonstruksi Nalar Arab Islam - Zaprulkhan Zaprulkhan (Scientia: Jurnal Hasil Penelitian, 2016)
Normatively, Islam not only has a single face that is transhistorical and transcendental, but its message is contextual and universal that transcends time and space. However, there are still very many Muslims who have the attachment is so strong in the past, so that they view tradition of early Islam as the prototype of the ideal face of Islam. For this group, the whole issues of Muslims have been discussed thoroughly by scholars predecessor, so our task now restates, or analogies in their opinions. Given Adonis, in the classic era, there are already established or are static thoughts (ats-Thabit) and creative or changed thoughts (al-mutahawwil). Established thoughts affirmed the only one true meaning to the text, and based on it; it becomes an epistemological authority. The character of dynamic thoughts is also grounded in the text, but through the open interpretation that is capable of responding to reality and change. Adonis recommended to develop creative thoughts; So they are always able to face various problems faced by the Muslims.